Exposure to acute air pollution and risk of bronchiolitis and otitis media for preterm and term infants. (June 2018) - Girguis, Mariam; Strickland, Matthew; Hu, Xuefei; Liu, Yang; Chang, Howard; Kloog, Itai; Belanoff, Candice; Bartell, Scott; Vieira, Verónica
Abstract Our aim is to estimate associations between acute increases in particulate matter with diameter of 2.5 µm or less (PM2.5 ) concentrations and risk of infant bronchiolitis and otitis media among Massachusetts births born 2001 through 2008.Our case-crossover study included 20, 017 infant bronchiolitis and 42, 336 otitis media clinical encounter visits. PM2.5 was modeled using satellite, remote sensing, meteorological and land use data. We applied conditional logistic regression to estimate odds ratios (ORs) and confidence intervals (CIs) per 10-µg/m3 increase in PM2.5. We assessed effect modification to determine the most susceptible subgroups. Infant bronchiolitis risk was elevated for PM2.5 exposure 1 day (OR = 1.07, 95% CI = 1.03–1.11) and 4 days (OR = 1.04, 95% CI = 0.99–1.08) prior to clinical encounter, but not 7 days. Non-significant associations with otitis media varied depending on lag. Preterm infants were at substantially increased risk of bronchiolitis 1 day prior to clinical encounter (OR = 1.17, 95% CI = 1.08–1.28) and otitis media 4 and 7 days prior to clinical encounter (OR = 1.09, 95% CI = 1.02–1.16 and OR = 1.08, 95% CI = 1.02–1.15, respectively). In conclusion, preterm infants are most susceptible to infant bronchiolitis and otitis media associated with acute PM2.5 exposures.